THE EFFECT OF CULTURE ON INTERNATIONAL NEGOTIATIONS: Communication styles, international negotiations, negotiators, significant role, British negotiation techniques, culture. - Nomozova, Maftuna; Jurayeva, Madina (Журнал иностранных языков и лингвистики, 2023)
The culture of negotiators can have a significant impact on the success of international negotiations. Culture influences communication styles, decision-making processes, and attitudes towards compromise and cooperation. In some cultures, direct communication and confrontation are valued, while in others, indirect communication and maintaining harmony are prioritized.